The Role Of Creativity In Entrepreneurship Development - Badrun, La Ode Muhammad; Syukur , La Ode Abdul (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2024)
Creativity entails the capacity to produce original and innovative ideas. Despite the plethora of imaginative concepts among entrepreneurs, many lack the essential skills to actualize them. This research aims to explore the impact of creativity on entrepreneurial advancement. Employing a literature review methodology, relevant scholarly articles were scrutinized to glean insights. Data collection relied on documentation techniques, and content analysis was employed for interpretation. To ensure precision and mitigate misinterpretation, thorough cross-referencing and validation from diverse sources were undertaken. The findings underscore that entrepreneurial creativity manifests in idea generation, proficient problem-solving, and innovative thinking. Creativity plays a pivotal role across various facets of entrepreneurial growth, encompassing product/service innovation, effective marketing and sales strategies, and adept business management. Consequently, creativity is regarded as indispensable for entrepreneurs, empowering them to tackle challenges and excel in a competitive business milieu